Factors contributing to delays in initiation of front-line cervical cancer therapy: disparities in a diverse south Florida population. Issue 11 (5th October 2022) - Roy, Molly; Finch, Lindsey; Kwon, Deukwoo; Jordan, Scott E; Yadegarynia, Sina; Wolfson, Aaron Howard; Slomovitz, Brian; Portelance, Lorraine; Huang, Marilyn
Abstract : Objective: Delay in initiating cervical cancer treatment may impact outcomes. In a cohort of patients initially treated by surgery, chemoradiation, chemotherapy, or in a clinical trial, we aim to define factors contributing to prolonged time to treatment initiation. Methods: Data from patients initiating treatment for cervical cancer at a single institution was abstracted. Time to treatment initiation was defined as the interval from the date of cancer diagnosis to the date of treatment initiation. Poisson regression model was used for analysis. Results: Of 274 patients studied, the median time to treatment initiation was 60 days (range 0–551). The median times to initiate surgery (54 days, range 3–96) and chemoradiation (58 days, range 4–187) were not significantly different (relative risk (RR) 1.01, 95% CI 0.98 to 1.04, p=0.54). The shortest median initiation time was for chemotherapy (47 days; RR 1.13, 95% CI 1.08 to 1.19, p<0.0001) and the longest was for clinical trial (62 days; RR 1.18, 95% CI 1.12 to 1.24, p<0.0001). Charity care (RR 1.09, 95% CI 1.05 to 1.14, p<0.0001), Medicare or Medicaid (RR 1.10, 95% CI 1.06 to 1.14, p<0.0001), and self-pay (RR 1.38, 95% CI 1.32 to 1.45, p<0.0001) delayed treatment initiation more than private insurance. Hispanic White women (RR 0.69, 95% CI 0.66 to 0.73, p<0.0001) had a shorter treatment initiation time compared with non-Hispanic White patients, while Afro-Caribbean/Afro-Latina women (RR 0.86, 95% CI 0.81 to 0.90, p<0.0001) and African-American patients (RR 1.13, 95% CI 1.07 to 1.19, p<0.0001) had longer initiation times. Spanish speaking patients did not have a prolonged treatment initiation (RR 0.68, 95% CI 0.66 to 0.71, p<0.0001), though Haitian-Creole speaking patients did (RR 1.07, 95% CI 1.01 to 1.13, p<0.002). Diagnosis at an outside institution delayed treatment initiation time (RR 1.24, 95% CI 1.18 to 1.30, p<0.0001) compared with diagnosis at the cancer center. Conclusion: Factors associated with prolonged time to treatment initiation include treatment modality, insurance status, language spoken, and institution of diagnosis. By closely examining each of these factors, barriers to treatment can be identified and modified to shorten treatment initiation time.